Permeability changes of integrin-containing multivesicular structures triggered by picornavirus entry. - Pan Soonsawad (2015)
Cellular uptake of clustered α2β1-integrin induces the formation of membrane compartments that subsequently mature into a multivesicular body (MVB). Enhanced internalization mediated by clustered integrins was observed upon infection by the picornavirus echovirus 1 (EVI). We elucidated the structural features of virus-induced MVBs (vMVBs) in comparison to antibody-induced control MVBs (mock infection) by means of high-pressure cryo fixation of cells followed by immuno electron tomography during early entry of the virus. Three-dimensional tomograms revealed a marked increase in the size and complexity of these vMVBs and the intraluminal vesicles (ILVs) at 2 and 3.5 hours post infection (p.i.), in contrast to the control MVBs without virus. Breakages in the membranes of vMVBs were detected from tomograms after 2 and especially after 3.5 h suggesting that these breakages could facilitate the genome release to the cytoplasm. The in situ neutral-red labeling of viral genome showed that virus uncoating starts as early as 30 min p.i., while an increase of permeability was detected in the vMVBs between 1 and 3 hours p.i., based on a confocal microscopy assay. Altogether, the data show marked morphological changes in size and permeability of the endosomes in the infectious entry pathway of this non-enveloped enterovirus and suggest that the formed breakages facilitate the transfer of the genome to the cytoplasm for replication.